Multimorbidity in Elderly Population: Challenges and Coping Strategies - ZHANG Yili, HUANG Xinyi, QI Baoyu, SUN Chuanrui, WANG Xiaoyang, WEI Xu, XIE Yanming (Zhongguo quanke yixue, 2022)
Multimorbidity has become a prominent public health problem in older people in China as the country reached an aging society. Summarizing the studies in multimorbidity in elderly population and analyzing and discussing the coping strategies are of great significance for comprehensive management of this group of people. Herein, we reviewed the latest studies about multimorbidity in older people involving management practice, diagnosis and treatment model, medication strategy, and the building of medical and nursing team and health management system. Besides that, we summarized the following coping strategies: establishing a patient-centered multimorbidity management research program, promoting the application of geriatric multimorbidity assessment tools, conduct research on the common etiology and pathogenesis of comorbidity, developing standardized guidelines/consensuses on multimorbidity management, formulating treatment schemes using the TCM ideas of "treating diseases according to syndrome" and "holistic treatment", Internet technologies and smart wearable devices, and conducting early risk assessment and management of multimorbidity. In addition, we provided a comprehensive outlook on future research directions. All this is aimed at providing a reference for further in-depth research in this field.